2022
DOI: 10.1002/cbdv.202200144
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thiophene/Furan‐Artemisinin Hybrid Molecules

Abstract: Natural products with semi-synthetic molecules displays higher biological activities, and creates new biological properties for the treatment of diseases. Although, natural products like artemisinin have been used as a traditional medicine over thousands of years, structure and biological properties of many natural products were investigated in the 20th century. Design and synthesis of new biologically active compounds including natural products have very critical roles to find novel drug candidates. Herein, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Furthermore, the reaction can also occur in moderate yields for aryl chlorides with substituents at the adjacent positions ( 7 , 56% yield). Notably, polyaromatic and heteroaromatic acyl chlorides, such as furan and thiophene, skeletons of which are widely distributed in bioactive molecules, were also applicable to this cascade three-component coupling, providing the heteroaryl ketones in moderate yields ( 15 – 17 ). Moreover, the protocol also exhibited superior chemoselectivity for chlorides in the presence of aryl chlorides ( 12 and 14 ).…”
mentioning
confidence: 99%
“…Furthermore, the reaction can also occur in moderate yields for aryl chlorides with substituents at the adjacent positions ( 7 , 56% yield). Notably, polyaromatic and heteroaromatic acyl chlorides, such as furan and thiophene, skeletons of which are widely distributed in bioactive molecules, were also applicable to this cascade three-component coupling, providing the heteroaryl ketones in moderate yields ( 15 – 17 ). Moreover, the protocol also exhibited superior chemoselectivity for chlorides in the presence of aryl chlorides ( 12 and 14 ).…”
mentioning
confidence: 99%
“…Thiophene, a five-membered ring structure containing a sulfur heteroatom, has been synthesized as a key scaffold in medicinal chemistry due to its diverse documented biological activities, including anticancer, antimicrobial, anti-inflammatory, and analgesic effects [ [41] , [42] , [43] , [44] , [45] ]. Thiophene derivatives, have been reported as anticancer agents via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, traditional Chinese medicines and targeted small molecules have been explored as potential therapeutic options for colorectal cancer by modulating this pathway [ 40 ]. Thiophene derivatives, known for their diverse biological activities, including antibacterial and anti-allergic properties, have also shown promising inhibitory effects against various cancers [ [41] , [42] , [43] , [44] , [45] ]. Based on our prior studies, a series of thiophene derivatives were built and their anti-proliferative efficacy was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Pepe et al reported a new artemisinin–chloroquine hybrid molecule that had higher activity than both the parent antiviral drugs. 3 CUDC-907 is a hybrid molecule obtained by integrating a HDAC inhibitory functionality (hydroxamic acid) into a core structural scaffold such as a PI3K inhibitor. It shows greater growth inhibition and proapoptotic activity than single-target PI3K or HDAC inhibitors and has been in clinical trials as the PI3K/HDAC inhibitor at Curis Inc. 2 b ,4 In general, molecular hybridization contributes to the development of multifunctional drugs and might overcome the problem of multidrug resistance.…”
mentioning
confidence: 99%